PENGARUH LAJU PERKEBUNAN KELAPA SAWIT TERHADAP PRODUKAI BAHAN PANGAN (PADI SAWAH DAN PADI LADANG) MASYARAKAT DI KECAMATAN RANAH BATAHAN TAHUN 2005-2017 - Asti Dora; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2020)
This stady aims to describe the influence of the rate of oil palm plantations on the production of food (paddy and paddy fields)of the community in Ranah Batahan sub-district in 2005-2017. The researcher aims to determine the rate of devolopment of oil palm plantations in Ranah Batahan realm district, the development of food crops (paddy and paddy fields) in the Ranah Batahan and adequacy of food production (paddy and paddy fields) in the Ranah Batahan sub-district. This type of research is quantitative descriptive unsing purposive sampling technigues. Where informations can be obtained from the head, staff, responsible person, head of the farmer grup, members of the UPT Balai Penyuluhan the area of Ranah Batahan districk counseling who as many as 100 research repondenst in the Ranah batahan domain. This researcher found that the conversion of oil palm plantations is growing rapidly every year while land area and food production lowland rice devolops every yer even though it is not as fast as oil palm ptantations while for paddy fields there is a decrease in both land area and production from year to year. While the adequacy of food production in Ranah Batahan subdistrict not the community. More that needs, namely rice that must be fulfilled by the community. This can be seen in terms of food availability or food security to be food insecure.